Digital Design with KP-Lab - Ponta, Domenico; Scapolla, Anna Marina (International Journal of Online and Biomedical Engineering (iJOE), 2007)
KP-Lab is an EU Integrated Project envisioning a learning system that facilitates innovative practices of sharing, creating and working with knowledge in education and workplaces. The project exploits a novel pedagogical view, the knowledge-creation metaphor of learning. According to such â??trialogical